2012
DOI: 10.1177/0021998312452896
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic interference shielding effectiveness, electrical resistivity and mechanical performance of carbonized medium density fiberboard

Abstract: The effect of carbonization temperature on the electromagnetic interference shielding effectiveness, electrical resistivity, and mechanical performance of medium density fiberboards carbonized in a vacuum furnace under a gas flow of nitrogen (200 mL/min) between 400℃ and 1500℃ was investigated. The medium density fiberboards specimens carbonized below 700℃ showed stable and low electromagnetic interference values (1.3–7.6 dB) between 10 MHz and 1 GHz frequency. The electromagnetic interference (average 43.1 dB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Similarly, Ren et al 17 synthesized CBC decorated with CoFe 2 O 4 nanocrystals by a solvothermal method; the composite exhibited excellent microwave absorption performance with a maximum RL of −45 dB at 8.6 GHz (2 mm) as the mass content of CBC/CoFe 2 O 4 is 10 wt %. Kwon et al 18 investigated the effect of carbonization temperature on the electromagnetic shielding effectiveness, resistivity, and mechanical performance of carbonized medium density fiber (MDF). The results indicated that the MDF carbonized below 700 °C shows the limited electromagnetic shielding values; however, it shows the high electromagnetic shielding values as the carbonization temperature is in the range of 900–1500 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Ren et al 17 synthesized CBC decorated with CoFe 2 O 4 nanocrystals by a solvothermal method; the composite exhibited excellent microwave absorption performance with a maximum RL of −45 dB at 8.6 GHz (2 mm) as the mass content of CBC/CoFe 2 O 4 is 10 wt %. Kwon et al 18 investigated the effect of carbonization temperature on the electromagnetic shielding effectiveness, resistivity, and mechanical performance of carbonized medium density fiber (MDF). The results indicated that the MDF carbonized below 700 °C shows the limited electromagnetic shielding values; however, it shows the high electromagnetic shielding values as the carbonization temperature is in the range of 900–1500 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the manufacturing of composite boards from charcoal powder is underway, and interest in carbonized material is increasing. Recently, authors have been conducting research to develop new carbonized boards with a similar performance to activated carbon boards and manufacturing simply by using a vacuum furnace without cracking and opening (Kwon et al 2012). Carbonized board could be transformed into other shapes due to its machinability, and it could be used in the electronic and construction industries (Kercher and Nagle 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In the authors' preliminary study, carbonized medium-density fiberboard (MDF) had significant performance on absorbing toxic materials, such as formaldehyde, benzene, and volatile organic compounds. In addition, the radon absorption performance of carbonized MDF at different temperatures was measured and it was concluded that the carbonization at 600 °C showed a higher radon absorption performance (Kwon et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…When the concentration of carbon material was 5wt% and 25wt%, the total insertion loss of electromagnetic wave in the frequency range of 2.5 GHz to 6 GHz could reach 20 dB to 40 dB [14]. Carbonized wooden material, such as solid wood panel [15] and fiberboard [16] could also improve SE, which could be further improved with structural designing. It was reported that the fiberboard composite designed with the metal net and conductive coating as reflective material on the two surface layers and barite powder and magnetite powder as an absorbing material in the core layer [17] could obtain an SE of more than 60 dB in the frequency range of 18.85 MHz to 1.46 GHz.…”
Section: Introductionmentioning
confidence: 99%